Field efficacy of pyrethroid treated plastic sheeting (durable lining) in combination with long lasting insecticidal nets against malaria vectors - Irish Seth R (Parasites & Vectors, 2010)
Abstract Background Insecticide treated plastic sheeting (ITPS), sometimes known as durable lining, has potential as a long-lasting insecticidal surface for malaria vector control when used as lining for interior walls and ceilings inside the home. Against a backdrop of increasing long lasting net (LN) coverage, we examined the effect of combining permethrin-treated plastic sheeting (ITPS) with LNs in Burkina Faso. Methods A verandah trap experimental hut trial of ITPS with or without Olyset LN was conducted in the Vallée du Kou near Bobo-Dioulasso, where the two molecular forms of Anopheles gambiae s.s., S (frequency 65%) and M (frequency 35%), occur. The S form is mostly pyrethroid resistant (Fkdr = 92%) owing to the kdr mechanism, and the M form is mostly kdr susceptible (Fkdr = 7%). The treatment arms included ITPS, Olyset, ITPS plus Olyset, ITPS plus untreated net (with or without holes), and untreated control. Results ITPS was significantly inferior to Olyset LN in terms of mortality (37% vs 63%), blood feeding inhibition (20% vs 81%) and deterrence (0 vs 42%) effects, and hence altogether inferior as a means of personal protection (16% vs 89%). The addition of ITPS to Olyset did not improve mortality (62%), blood feeding inhibition (75%), deterrence (50%) or personal protection (88%) over that of Olyset used alone. Use of untreated nets - both holed and intact - with ITPS provided greater protection from blood-feeding. The intact net/ITPS combination killed more mosquitoes than ITPS on its own. Conclusions Although ITPS has a potential role for community control of malaria, at low coverage it is unlikely to be as good as Olyset LNs for household protection. The combination of pyrethroid IRS and pyrethroid LN - as practiced in some countries - is unlikely to be additive except, perhaps, at high levels of IRS coverage. A combination of LN and ITPS treated with an alternative insecticide is likely to be more effective, particularly in areas of pyrethroid resistance.